Changes in gene expression of histone modification enzymes in rat granulosa cells undergoing luteinization during ovulation. Issue 1 (December 2016) - Maekawa, Ryo; Lee, Lifa; Okada, Maki; Asada, Hiromi; Shinagawa, Masahiro; Tamura, Isao; Sato, Shun; Tamura, Hiroshi; Sugino, Norihiro
Abstract Background The ovulatory LH surge rapidly alters the expression of steroidogenesis-related genes such as steroidogenic acute regulatory protein (StAR ) in granulosa cells (GCs) undergoing luteinization. We recently reported that histone modifications contribute to these changes. Histone modifications are regulated by a variety of histone modification enzymes. This study investigated the changes in gene expression of histone modification enzymes in rat GCs undergoing luteinization after the induction of ovulation. The extracellular regulated kinase (ERK)-1/2 is a mediator in the intracellular signaling pathway stimulated by the ovulatory LH surge and regulates the expression of a number of genes in GCs. We further investigated whether ERK-1/2 is involved in the regulation of the histone modification at theStAR promoter region in GCs undergoing luteinization. Results GCs were obtained from rats treated with equine chorionic gonadotropin (CG) before (0 h) and after human (h) CG injection. The expressions of 84 genes regulating histone modifications or DNA methylation were measured using a PCR array. Five genes (HDAC4, HDAC10, EZH2, SETDB2, and CIITA ) were identified as histone acetylation- or histone methylation-related genes, and were significantly altered after hCG injection. None of the genes were related to DNA methylation. mRNA levels ofEZH2, SETDB2, HDAC4, andHDAC10 decreased andCIITA mRNA levels increased 4 or 12 h after hCG injection. GCs isolated after eCG injection were incubated with hCG for 4 h to induce luteinization.StAR mRNA levels were significantly increased by hCG accompanied by the increase in H3K4me3 of theStAR promoter region.StAR mRNA expression was inhibited by the ERK inhibitor with the significant decrease of H3K4me3. These results suggest that hCG increasesStAR gene expression through the ERK-1/2-mediated signaling which is also associated with histone modification of the promoter region. Conclusions Gene expressions of histone modification enzymes change in GCs undergoing luteinization after ovulation induction. This change may play important roles in regulating the expression of various genes during the early stage of luteinization, which may be critical for the subsequent corpus luteum formation.